Gender and Serious Youth Victimization: Assessing the Generality of Self-Control, Differential Association, and Social Bonding Theories - Alarid, Leanne F. (2019)
Criminologists have long questioned whether theories that have focused on male delinquency are equally applicable to female delinquency, a phenomenon termed “gender generalizability.” While a number of studies have used self-reports from offenders, criminologists have yet to extend this issue to crime victims. While controlling for variables derived from victimization theories, we test three criminological perspectives (self-control, differential association, and social bond) on male and female victimization using data obtained from the Evaluation of the Gang Resistance Education and Training (GREAT) Program in the United States. Results show that for male victimization, gang membership and indications of a deviant lifestyle (self-reported delinquency) significantly predicted victimization, while associating with pro-social peers and being in a gang were associated with female victimization. Parental monitoring and belong to an intact family reduced victimization for males. Self-reported delinquency consistently predicted victimization across genders